Efficacy and safety of sintilimab combined with trastuzumab and chemotherapy in HER2-positive advanced gastric or gastroesophageal junction cancer - Liu, Zeyu; Liu, Aina; Li, Ming; Xiang, Jinyu; Yu, Guohua; Sun, Ping (Frontiers in Immunology, 2025)
BackgroundTo evaluate the efficacy and safety of sintilimab in combination with trastuzumab and chemotherapy for HER2-positive advanced gastric/gastroesophageal junction cancer (GC/GEJC).MethodsHER2-positive advanced GC/GEJC patients admitted to our department between January 2018 and October 2024 were included in this study. Patients who received sintilimab in combination with trastuzumab and chemotherapy were assigned to cohort A, while patients who received trastuzumab and chemotherapy alone were assigned to cohort B. The primary endpoints were progression-free survival (PFS) and overall survival (OS), while the secondary endpoints included disease control rate (DCR), objective response rate (ORR), and safety.ResultsA total of 103 patients were analyzed, with 46 in cohort A and 57 in cohort B. The ORR was 65.2% in cohort A compared to 40.4% in cohort B, while the DCR was 87.0% in cohort A and 70.2% in cohort B. The median follow-up duration was 14.0 months. Median PFS (mPFS) was 9.4 months (95% CI: 5.6–13.2) for cohort A and 7.4 months (95% CI: 6.1–8.7) for cohort B (p = 0.089). Median OS (mOS) was 16.4 months (95% CI: 11.5–21.3) in cohort A versus 14.2 months (95% CI: 11.2–17.2) in cohort B (p = 0.069). Adverse events were predominantly mild, and no treatment-related deaths occurred.ConclusionSintilimab combined with trastuzumab and chemotherapy showed promising efficacy and acceptable safety in HER2-positive advanced GC/GEJC. However, no statistically significant improvement in survival outcomes was observed compared to trastuzumab and chemotherapy alone.